Do clinical safety charts improve paramedic key performance indicator results? (A clinical improvement programme evaluation). Issue 7 (8th November 2010) - Ebbs, Phillip; Middleton, Paul M; Bonner, Ann; Loudfoot, Allan; Elliott, Peter
Abstract : Introduction: Is the Clinical Safety Chart clinical improvement programme (CIP) effective at improving paramedic key performance indicator (KPI) results within the Ambulance Service of New South Wales? Methods: The CIP intervention area was compared with the non-intervention area in order to determine whether there was a statistically significant improvement in KPI results. Results: The CIP was associated with a statistically significant improvement in paramedic KPI results within the intervention area. Conclusions: The strategies used within this CIP are recommended for further consideration.